Preventing Terrorism among Ghanaian Muslim Youth: Realities and Challenges - Mohammed, Zulkarnain; Abubakar, Mohamad Zaini (School of Social Sciences, USM, 2017)
Although extremism is an old phenomenon, the pursuit to find measures to combat it reached an upsurge after the major attacks in many European countries and America, leading many countries and the international community to take severe measures to prevent this menace. Over the past couple of decades, Ghana has won a hard-earned reputation as a stable and settled product of democracy. Despite these efforts, the African continent is plagued in recent times with Muslim radicals and terrorists 19 activities from some militant groups such as the AQIM, Boko Haram, Ansar Dine and MUJAO. While Ghana has been far from being victims of any such attacks and consequently recorded no valid cases about Ghanaian Muslim youth involvement in such acts; Ghana 19s location in the West African region renders the country 19s youth more vulnerable to terrorist recruitment. This concept paper therefore assesses the possibility of Ghana 19s Muslim youth becoming a target of terrorist recruitment and possibly launching attacks or serving some major terrorist group across the region. It also examines some of the challenges faced by Muslim religious leaders in fighting against extremism and radicalization. Analyses of secondary data revealed that, there are no Muslims terrorist cells currently operating in Ghana. However, certain conditions prevailing in the country heighten the possibility of becoming a target of terrorism or a safe haven for terrorist groups. The analyses further proved that, Ghana has put in place measures such as legislations and institutions to ensure that any terrorist attempt at the country is averted. The paper finally offered some recommendations for policy consideration which include among others, granting a semi-autonomous status to some local Islamic organizations to work hand-in-hand with governmental institutions to alleviate any threats from Ghanaian Muslim youth extremists.